Right-of-way licensing ordinances: renewing city authority over energy utilities to facilitate climate policy - Christy Anderson Brekken; Roman Patchell; Julia Mycek (Frontiers in Sustainable Cities)
In the state of Oregon and across the United States, municipal governments have traditionally granted utilities the right to use the public right-of-way through negotiated franchise agreements which set contractual conditions of use for 10 or more years. However, franchise agreements typically have terms that create a barrier to implementation of climate policy in cities. For over 2 decades, Oregon cities have innovated a new regulatory approach by adopting utility right-of-way licensing ordinances. To investigate the performance of the new licensing ordinance governance structure, we interviewed 12 city employees engaged in right-of-way management. Four of these cities use franchise agreements, eight administer licensing ordinances; nearly all have experience with both structures. We compared city staffs' experiences and perceptions of each governance structure across three dimensions of institutional theory: legal relations, transaction costs, and social norms. We found that city staff overwhelmingly prefer licensing ordinances as a right-of-way governance structure and adoption seems to be growing. Primary motivations include reducing city expenses through efficient use of staff time, equitable treatment of utility providers, and the exercise of city authority over the right-of-way to achieve a variety of city goals. City climate goals are not explicitly articulated as a motivation for licensing ordinance adoption; however, city staff gave several examples of how the licensing ordinance facilitates climate policy implementation. This is the first study of licensing ordinances in the literature; future studies may more directly link municipal regulation of the right-of-way to city climate policy.